ANALISIS REAKSI INVESTOR TERHADAP PENERIMAAN LAPORAN OPINI AUDIT GOING CONCERN - Indriani, Widya; Ratmono, Dwi (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to obtain empirical evidence on investor reaction to going concern audit reports. Investor reaction is measured by cumulative abnormal return (CAR) with the market adjusted model. Institutional ownership is used as a moderating variable. This research hypothesized that going concern audit reports, going concern audit reports that cited financing problems, and going concern audit reports moderated by institutional ownership have negative influence on investor reaction.The sample in this research is all firms listed in Indonesia Stock Exchange during 2008-2013 that received going concern audit reports. The sampling method is purposive sampling, with the final sample is 95 firms. The hypothesis tested using multiple regression with OLS assumptions and one-sample t-test.The result indicates going concern audit report has a significant negative influence on investor reaction. Going concern audit reports that cited financing problems have no significant influenced on investor reaction. Institutional ownership can’t strengthen the influence of going concern audit reports on the investor reaction.